Implementation of Steganographic Model using Inverted LSB Insertion - Shubhangi D. Kamat; Prof. S.S. Patil; Prof. A.S. Mali (International Journal of Engineering and Management Research, 2018)
The most important thing in this insecure world is the secrecy of everything. In today’s world, any important data costs more than money. Steganography is the technique in which one can hide data as a secrete in selected image. In case of spatial domain, LSB approach is most popular in steganography, where all the LSBs of pixels of image are replaced by the bits of secret data. But the problem is that the secrete can be easily guessed by the hacker and the data is obtained by extracting it from direct LSBs. To make the system more robust and to improve the signal to noise ratio, the conventional LSB insertion method is replaced by inverted LSB technic. The decision to invert or not the LSB depends on combination of the 2nd and 3rd LSB. As not each and every LSB is inverted, it makes the steganalysis very difficult.